Photosensitive porous silicon based structures - Svechnikov, S.V.; Kaganovich, E.B.; Manoilov, E.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
We present results of electrical and photoelectrical measurements on two types of Al/porous silicon (PS)/monocrystalline silicon (c-Si)/Al sandwich structures with thin and thick PS layers obtained by stain etching. Current-voltage characteristics and photosensitivity spectra indicate that for structures with a thin PS layer the photosensitivity is determined by PS/c-Si heterojunctions (HJ), while for structures with a thick PS layer – by the PS layers themselves. The properties of PS/c-Si HJ were explained in the framework of a band diagram of the isotype HJ with opposite band bendings on the sides due to a high concentration of defect centers at the heterointerface. PS layers exhibit photoconduction with the photosensitivity maximum at 400–500 nm. The results are compared with those obtained for the structures based on PS layers prepared by electrochemical anodization.